Behind Altruism: Posey’s Willingness to Sacrifice in Mitch Albom’s Novel “For One More Day” - Ramadhani, Riska Dewi; Hakim, Novanda Lukwita; Ramadhani, Nasywa Nuzula; Rahmadianti, Happy Julia; Pasopati, Rommel Utungga (Lia Center of Research and Education, 2025)
This paper examines Posey's selfless actions, namely her readiness to make sacrifices, as a major character in Mitch Albom's For One More Day. Emotional empathy and a strong moral commitment are frequently present in altruism, which is characterized as unselfish care for the welfare of others. This study uses a qualitative yet psychological literary analysis to look at how Posey's self-sacrificing actions, whether they be financial, emotional, or physical, show what true altruism is all about. Posey continuously puts the needs of others before her own, from taking on dual parental responsibilities to facing social shame and working nonstop to maintain her family. The results demonstrate that Posey's sacrifices are based on resilience, responsibility, and true love. Her character serves as a reflection of the transforming potential of caring and emphasizes the inner strength needed to continuously give without expecting anything in return.